Analysis of Implementation of the World Cooperation SMK Enterprises/ Analisis Pelaksanaan Kerjasama SMK dengan Dunia Usaha - Dewi Kurniasari; Gatot Isnani (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2015)
The absorption of graduates at SMK Negeri 3 Malang in the past three years has increased. The majority of the students have been accepted in the business world/industry, and the remaining graduates are not absorbed in the business/industry choose to self-employed or continue their studies in Higher Education. Promoting school graduates in business/industry by using students practice and alumni as a real promotional tool. In addition, electronic media such as websites and television such as general overview information about SMK Negeri 3 Malang. Suggestions in this study are: (1) The school should need to e-collaborate with the industrial world in accordance with the program expertise to channel the school graduates according to predetermined targets; (2) The research finding can be used as additional reference research within the scope of the current vocational education that is smaller than the reference research within the scope of general education; (3) This study can be used for future researchers on the relationship between school partnership with the number of unemployed in Indonesia. AbstrakKeterserapan lulusan SMK Negeri 3 Malang dalam tiga tahun terakhir mengalami peningkatan. Mayoritas sudah diterima di dunia usaha/industri, dan sisanya lulusan yang tidak terserap dalam dunia usaha/industri memilih untuk berwirausaha atau melanjutkan studinya ke Perguruan Tinggi. Sekolah mempromosikan lulusan dalam dunia usaha/industri adalah dengan menggunakan siswa prakerin dan alumni sebagai alat promosi yang nyata. Selain itu menggunakan media elektronik berupa website dan televisi yang memuat informasi gambaran secara umum tentang SMK Negeri 3 Malang. Saran dalam penelitian ini adalah (1) Sebaiknya pihak sekolah perlu lebih memperbanyak kerjasama lagi dengan pihak dunia industri yang sesuai dengan program keahlian yang dimiliki sekolah guna tersalurnya lulusan sesuai dengan target yang telah ditentukan. (2) Dapat dijadikan tambahan referensi penelitian dalam ruang lingkup pendidikan SMK yang saat ini lebih kecil daripada referensi penelitian dalam lingkup pendidikan umum. (3) Dapat digunakan untuk penelitian selanjutnya mengenai hubungan antara kemitraan sekolah dengan jumlah pengangguran di Indonesia.